Pembatalan Perkawinan karena Paksaan Orang Tua Analisis Putusan Pengadilan Agama Palembang Nomor 360/Pdt.G/2025/PA.PLG - Dea Putri Ananda; Eliyani; Anggi Saputra; Muhammad Fakhruzzaini (Jurnal Teologi Islam, 2026)
Marriage under Indonesian law must be based on the consent of both prospective spouses, as stipulated in Article 6 paragraph (1) of Law Number 1 of 1974 on Marriage. However, in practice, marriages are still conducted under coercion from family members. This study aims to analyze the judicial considerations in the Decision of the Religious Court of Palembang Number 360/Pdt.G/2025/PA.PLG concerning the annulment of marriage due to parental coercion imposed on one of the parties. The research method applied is normative juridical with a case approach. The findings show that the marriage between the Plaintiff and the Defendant did not meet the legal requirements of validity because it was not founded on free will but rather influenced by familial pressure. The panel of judges considered witness testimonies, written evidence, and psychological examination results to establish that the marriage had been conducted without the Defendant’s full consent. This ruling is consistent with Article 71 letter (f) and Article 73 letter (b) of the Compilation of Islamic Law, which provide the legal basis for annulment in cases of coercion. In conclusion, the judges emphasized the principle of substantive justice through the fiqh maxim dar’ul mafasid muqaddamun ‘ala jalbil mashalih, meaning that preventing harm takes precedence over attaining benefit. The implication of this decision underscores the urgency of free consent as the foundation of marriage and highlights the need for legal protection of individuals harmed by forced marriage practices.